(untitled) (Global Journal of Management and Business Research, 2024)
The current research explores the latent drivers of job satisfaction in Trinidad and Tobago The aim is to determine the construct validity of the Hackman Oldham 1975 Job Characteristics Model JCM to measure job satisfaction Data was collected from employees using the cross-sectional research method and conveniently sampled from twelve 12 service institutions The twelve 12 service institutions span three sectors information and communications technology ICT tertiary education and public utilities These three 3 sectors were chosen because they represent the three most significant sectors in the Trinidad and Tobago economy and three 3 different levels of industry Using three 3 different sectors in research enhances generalizability by providing a more diverse sample reducing the risk of bias and increasing the likelihood that findings can be applied to a broader range of contexts or populations The service institutions include TSTT FLOW and DIGICEL Information and Communications Technology UTT UWI SBCS ALJ-GSB SAMS-TT and CTS-CBS Leaders in Tertiary Education WASA T TEC and PTSC Public Utilities These service institutions were purposely chosen because they represent the top-performing companies in their respective industries